1983
DOI: 10.1016/0014-5793(83)80980-6
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies for the detection and quantitation of the endogenous plant growth regulator, abscisic acid

Abstract: Monoclonal antibodies (mAB) have been produced which recognize the physiologically active 2‐cis‐(S‐form of the endogenous plant growth regulator, abscisic acid (ABA). Cross‐reaction with the ABA‐catabolites, phaseic and dihydrophaseic acid, is negligible, and (R)‐ABA, 2‐trans‐ABA, the ABA‐conjugate, ABA‐β‐D‐glucopyranosyl ester, as well as the putative ABA precursor, xanthoxin, are totally unreactive. In addition to being very specific, the mAB exhibit high affinites for 2‐cis‐(S)‐ABA: the K values were 7.9 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
1
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(96 citation statements)
references
References 12 publications
5
89
1
1
Order By: Relevance
“…As shown in Figure 3 such deviations could not be observed in the test extract. Together with the data shown in Figure 2, the results show that combination of separation techniques with ELISA (17) and IAA (18). In these studies, it became clear that the selection of mAB with specificities rivaling or even surpassing those of antisera is possible.…”
Section: -(2-ethylhexylamino)-2-methylpyrollo-[23-d]-pyrimidine and supporting
confidence: 57%
See 2 more Smart Citations
“…As shown in Figure 3 such deviations could not be observed in the test extract. Together with the data shown in Figure 2, the results show that combination of separation techniques with ELISA (17) and IAA (18). In these studies, it became clear that the selection of mAB with specificities rivaling or even surpassing those of antisera is possible.…”
Section: -(2-ethylhexylamino)-2-methylpyrollo-[23-d]-pyrimidine and supporting
confidence: 57%
“…In these studies, it became clear that the selection of mAB with specificities rivaling or even surpassing those of antisera is possible. It was furthermore shown that, by employing appropriate screening protocols, the selection of high affinity mAB is possible (17,18). Both specificity and affinity need to be maximized in order to allow for optimum immunoassay performance.…”
Section: -(2-ethylhexylamino)-2-methylpyrollo-[23-d]-pyrimidine and mentioning
confidence: 99%
See 1 more Smart Citation
“…The ELISA was performed as described by Walker-Simmons (28) with the monoclonal antibody of Mertens et al (11), which was purchased from Idetek (San Bruno, CA). The ABA-4'-conjugate was prepared according to Weiler (29).…”
Section: Growth Of Plantsmentioning
confidence: 99%
“…Levels of endogenous abscisic acid were determined for replicate batches of five embryos by ELISA, using an abscisicacid-specific monoclonal antibody developed specifically for ELISA [20] and obtained from Idetek Inc. (San Bruno, CA, USA). The procedures followed for the extraction of abscisic acid and the determination of its concentration by ELISA have been comprehensively detailed elsewhere [21].…”
Section: Invnunoassuy Qf Uhscisic Cicidmentioning
confidence: 99%